Boron nitride composite particles, their production method, and resin composition
Patent Information
- Application Number
- JP2021130113
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-06
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-08-06
Smart Images

Figure 0007652656000002 
Figure 0007652656000003 
Figure 0007652656000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to boron nitride composite particles, a method for producing the same, and a resin composition. [Background technology]
[0002] Electronic components such as transistors, thyristors, and CPUs are required to efficiently dissipate heat generated during use. Heat dissipation members having high thermal conductivity are used together with such electronic components. Meanwhile, boron nitride particles have high thermal conductivity and high insulating properties, and are therefore widely used as a filler in heat dissipation members. For example, Patent Document 1 proposes a hexagonal boron nitride powder that, when used as a filler in insulating heat dissipation materials such as resins, can increase the thermal conductivity and withstand voltage (dielectric breakdown voltage) of the resins, and a method for producing the same.
[0003] In recent years, devices equipped with electronic components have been increasing in signal transmission speed and capacity. For this reason, heat dissipation members are also required to have properties that can respond to the above-mentioned trends. Specifically, heat dissipation members with small dielectric tangents are desirable. As a method for lowering the dielectric tangent of a heat dissipation member, for example, it is possible to use a resin with a small dielectric tangent. However, liquid crystal polymers and fluororesins, which are known as resins with low dielectric tangents, are insufficient in processability, thermal properties, mechanical properties, etc. for the intended use, although they have low dielectric tangents. Therefore, from the viewpoint of improving thermal properties, fillers are generally used.
[0004] Since boron nitride is a material with a relatively small relative dielectric constant, its use as a filler for obtaining a heat dissipation component with a low dielectric loss tangent has been considered. For example, Patent Document 2 describes a dielectric resin composition containing an inorganic substance dispersed in a thermoplastic resin and / or a thermosetting resin, the inorganic substance containing plate-like inorganic particles, the inorganic particles having a material selected from the group consisting of hexagonal boron nitride, aluminum oxide, talc, and mica, and the dielectric resin composition has a relative dielectric constant ε of 5 or less and a dielectric loss tangent tanδ of 5×10 at a frequency of 1 GHz or more and a temperature of 25° C. -4 A resin composition for dielectrics has been proposed, which is characterized by the following: [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-116401 A [Patent Document 2] JP 2015-040296 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, hexagonal boron nitride itself is excellent in stability, and does not necessarily have a high affinity with resin. According to the study by the present inventors, in a laminate prepared by forming a sheet-shaped molded body from a resin composition containing hexagonal boron nitride as described above and bonding it to a different material such as a metal plate, it has been found that, for example, when thermal stress occurs inside the laminate due to a heat cycle test or the like, peeling may occur between the resin and the primary particles of hexagonal boron nitride inside the molded body before peeling occurs at the interface between the molded body and the laminate. In a heat dissipation member prepared using a resin composition containing hexagonal boron nitride, there may be cases in which the durability as a heat dissipation member is not sufficient. In addition, the affinity between the resin and the primary particles of hexagonal boron nitride is low, and voids or the like are generated, which may lead to a decrease in heat dissipation as a heat dissipation member.
[0007] As a method for improving the affinity between the primary particles of hexagonal boron nitride and resin, for example, since the side surfaces of the primary particles of hexagonal boron nitride have functional groups, a method of increasing the thickness of the primary particles in order to increase the ratio of the side surfaces per particle is conceivable. However, it is not easy to grow the primary particles of hexagonal boron nitride in the thickness direction and directly obtain hexagonal boron nitride particles having a thickness of a predetermined value or more.
[0008] The present disclosure aims to provide novel composite particles of boron nitride, which are composed of boron nitride, have improved affinity with resins, and exhibit excellent heat dissipation properties when a resin composition is prepared. The present disclosure also aims to provide a method for producing such composite particles. The present disclosure also aims to provide a resin composition containing the composite particles. [Means for solving the problem]
[0009] One aspect of the present disclosure provides a boron nitride composite particle comprising a first particle of hexagonal boron nitride and a plurality of second particles of hexagonal boron nitride having a smaller particle size than the first particle and attached to a (001) face of the first particle, wherein the sum of the length of the (100) face of the first particle and the length of the (100) face of the second particle relative to the perimeter in a cross section perpendicular to the (001) face of the first particle is 5.0% or more and the average thickness is 0.5 μm or more.
[0010] The boron nitride composite particle includes a first particle and a second particle of hexagonal boron nitride, and the second particle is attached to the (001) face of the first particle, so that the thickness of the composite particle is large, 0.5 μm or more. The thickness of the primary particle of hexagonal boron nitride is generally about 0.3 μm. In addition, in the cross section of the composite particle, the total value of the length of the (100) face (face corresponding to the side face of the primary particle) of the first particle and the second particle is 5% or more of the perimeter of the composite particle, so that the side face per composite particle is sufficiently secured, and the affinity with the resin can be improved. Therefore, the boron nitride composite particle is excellent as a filler for a resin composition, and the obtained resin composition can exhibit excellent heat dissipation properties.
[0011] The first particle and at least a part of the second particle may be in contact with each other through their (001) faces. By contacting the first particle and the second particle of hexagonal boron nitride with each other through their (001) faces, the adhesion between them becomes stronger, and the (100) face of the second particle attached to the first particle can be directed toward the outside of the composite particle, thereby further improving the affinity with the resin.
[0012] The first particles may have an average particle size of 20.0 μm or less.
[0013] The number of the second particles attached to the first particle may be 50 or more per one first particle.
[0014] One aspect of the present disclosure provides a resin composition comprising a resin and the above-described boron nitride composite particles.
[0015] The resin composition contains the above-mentioned boron nitride composite particles, and therefore has excellent affinity between the resin and the boron nitride composite particles. Therefore, for example, in a laminate prepared by forming a sheet-shaped molded body from the resin composition and bonding it to a different material such as a metal plate, even if thermal stress or the like occurs, destruction inside the molded body can be suppressed. In other words, by using the above-mentioned resin composition, a heat dissipation member with excellent durability can be molded. Similarly, the resin composition contains the above-mentioned boron nitride composite particles, and therefore has excellent affinity between the resin and the boron nitride composite particles, and when a molded body is formed using the resin composition, it can exhibit excellent heat dissipation properties.
[0016] One aspect of the present disclosure provides a method for producing boron nitride composite particles, comprising the steps of: dispersing a powder containing first particles of hexagonal boron nitride and second particles of hexagonal boron nitride having a particle size smaller than that of the first particles, in a solvent containing an alcohol having a carbon number of 5 or less to obtain a dispersion; and reducing the content of the solvent from the dispersion and attaching one or more of the second particles onto the (001) plane of the first particles, to obtain composite particles.
[0017] The method for producing the boron nitride composite particles includes a step of dispersing primary particles (first particles and second particles) of hexagonal boron nitride having different particle sizes in a solvent containing an alcohol having a carbon number of 5 or less. After the second particles are sufficiently individually dispersed in this step, the solvent is reduced, and the second particles can be attached to the (001) plane of the first particles by utilizing the intermolecular forces between the first particles and the second particles. In this way, the boron nitride composite particles as described above can be produced.
[0018] The step of obtaining the composite particles may be a step of attaching the (001) plane of the second particle to the (001) plane of the first particle. By adjusting the dispersion state and the solvent reduction conditions, the first particle and the second particle can be adjusted so that the (001) planes of the first particle and the second particle are attached to each other.
[0019] The content of the alcohol in the solvent may be 50% by volume or more. When the content of the alcohol in the solvent is within the above range, the dispersion state of the secondary particles of boron nitride can be made more uniform, making it easier to produce the composite particles.
[0020] The alcohol may include at least one selected from the group consisting of ethanol, 1-propanol, and 2-butanol. By including such an alcohol as the alcohol when preparing the dispersion, aggregation of the second particles having a small particle size in the dispersion can be suppressed, and adhesion between the (001) faces of the first particles and the second particles can be facilitated.
[0021] The amount of the secondary particles may be 10 to 50 parts by mass with respect to 100 parts by mass of the primary particles. When the amount of the secondary particles is within the above range, aggregation of the secondary particles can be suppressed.
[0022] The step of obtaining the dispersion may be a step of mixing the powder with the solvent and carrying out a dispersion treatment for 30 minutes or more. Effect of the Invention
[0023] According to the present disclosure, it is possible to provide novel composite particles of boron nitride that are composed of boron nitride, have improved affinity with resin, and exhibit excellent heat dissipation when a resin composition is prepared. According to the present disclosure, it is also possible to provide a method for producing the composite particles described above. According to the present disclosure, it is also possible to provide a resin composition containing the composite particles described above. [Brief description of the drawings]
[0024] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a boron nitride composite particle. [Diagram 2] FIG. 2 is a schematic cross-sectional view for explaining the perimeter of a boron nitride composite particle. [Diagram 3] FIG. 3 is a schematic cross-sectional view illustrating the sum of the length of the (100) plane of the first particle and the length of the (100) plane of the second particle 20 in a boron nitride composite particle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings as appropriate. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents. In the description, the same reference numerals are used for the same elements or elements having the same functions, and redundant descriptions are omitted as the case may be. In addition, positional relationships such as up, down, left, and right are based on the positional relationships shown in the drawings, unless otherwise specified. Furthermore, the dimensional ratios of each element are not limited to those shown in the drawings.
[0026] Unless otherwise specified, the materials exemplified in this specification can be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.
[0027] One embodiment of the boron nitride composite particle is a composite particle including a first particle of hexagonal boron nitride and a plurality of second particles of hexagonal boron nitride smaller in size than the first particle and deposited on a (001) face of the first particle.
[0028] Fig. 1 is a schematic cross-sectional view showing an example of a boron nitride composite particle. The schematic cross-sectional view shown in Fig. 1 is a cross section perpendicular to the (001) plane of a first particle of hexagonal boron nitride constituting a boron nitride composite particle 100. The boron nitride composite particle 100 has a first particle 10 of hexagonal boron nitride and a second particle 20 of hexagonal boron nitride, and a plurality of second particles 20 are attached to the first particle 10. Fig. 1 shows an example of a boron nitride composite particle in which both the first particle 10 and the second particle 20 are attached on the (001) plane.
[0029] The first particle 10 and the second particle 20 of hexagonal boron nitride are both primary particles of hexagonal boron nitride and are scale-shaped particles. The purity of the hexagonal boron nitride may be higher, for example, 99.5% by mass or more, or 99.8% by mass or more.
[0030] The purity of hexagonal boron nitride in this specification means a value calculated by titration. More specifically, boron nitride is first decomposed with sodium hydroxide using an alkali, and ammonia is distilled from the decomposition liquid by steam distillation and collected in an aqueous boric acid solution. This collected liquid is then titrated with a normal sulfuric acid solution. The content of nitrogen atoms (N) in the boron nitride powder is calculated from the titration results. From the content of nitrogen atoms obtained, the content of hexagonal boron nitride (hBN) in the boron nitride is determined based on the following formula (1), and the purity of hexagonal boron nitride can be calculated. The formula weight of hexagonal boron nitride is 24.818 g / mol, and the atomic weight of nitrogen atoms is 14.006 g / mol. Hexagonal boron nitride (hBN) content in sample [mass%] = nitrogen atom (N) content [mass%] × 1.772 (1)
[0031] In the boron nitride composite particle 100, the total value of the length of the (100) plane of the first particle 10 and the length of the (100) plane of the second particle 20 relative to the perimeter in a cross section perpendicular to the (001) plane of the first particle 10 is 5.0% or more. The lower limit of the total value of the length of the (100) plane of the first particle 10 and the length of the (100) plane of the second particle 20 may be, for example, 10.0% or more, 15.0% or more, or 20.0% or more based on the perimeter of the boron nitride composite particle 100. When the total value is within the above range, the number of functional groups per boron nitride composite particle 100 can be increased, the affinity with resins and the like can be further improved, and the heat dissipation property can be further improved when a resin composition is prepared. Examples of the functional group include an OH group and an NH group. The upper limit of the total length of the (100) plane of the first particle 10 and the (100) plane of the second particle 20 may be, for example, 50.0% or less, 40.0% or less, or 30.0% or less based on the perimeter of the boron nitride composite particle 100. When the total value is within the above range, it is possible to suppress an increase in viscosity of the resin composition when the boron nitride composite particle is added to the resin. The total value of the length of the (100) plane of the first particle 10 and the length of the (100) plane of the second particle 20 relative to the perimeter in a cross section perpendicular to the (001) plane of the first particle 10 may be adjusted within the above range, and may be, for example, 5.0 to 50.0%, 10.0 to 40.0%, or 20.0 to 30.0%.
[0032] In this specification, the total value of the length of the (100) plane of the first particle and the length of the (100) plane of the second particle relative to the above-mentioned perimeter length means a value measured by the following method. In the case of a composite particle composed of particles having a scale shape such as a primary particle of hexagonal boron nitride, when measuring the total value of the length of the (100) plane of the first particle and the length of the (100) plane of the second particle, an error is likely to occur when an image including a particle image taken by an electron microscope is analyzed as it is (for example, a measurement error occurs when the particle is tilted), making accurate measurement and evaluation difficult. Therefore, the measurement of the total value of the length of the (100) plane of the boron nitride composite particle in this specification is performed by the following method. First, 3 g of boron nitride composite particles are molded to 30 mmφ at a pressure of 5 MPa using a press molding machine, and a molded body is formed by embedding the molded body in a resin. The obtained molded body is subjected to cross-sectional milling in a direction parallel to the direction in which pressure is applied to obtain a cross section of the boron nitride composite particle. Since the press molding can obtain a state in which the boron nitride composite particles are oriented in one direction, measurement errors due to the particles being tilted relative to the measurement surface can be suppressed. The cross section obtained by the cross section milling process is photographed by a scanning electron microscope, and the SEM image including the obtained particle image is imported into image analysis software. Next, from the imported image, the perimeter of the boron nitride composite particle, the length of the (100) face of the first particle, and the length of the (100) face of the second particle are measured. The same measurement is performed for 100 boron nitride composite particles, and the arithmetic average value is calculated and the total value is obtained. As the press molding machine, for example, "BRE-32" (trade name) manufactured by Rigaku Corporation can be used. As the resin, for example, "G2 Epoxy" (trade name) manufactured by GATAN Co., Ltd. can be used. As the scanning electron microscope, for example, "JSM-6010LA" (trade name) manufactured by JEOL Ltd. can be used. As the image analysis software, for example, "Mac-View" (trade name) manufactured by Mountec Co., Ltd. can be used.
[0033] The perimeter of the boron nitride composite particle 100 means the outer circumference. FIG. 2 is a schematic cross-sectional view for explaining the perimeter of the boron nitride composite particle. For simplicity, FIG. 2 shows an example in which one or two second particles 20 are attached to the first particle 10. FIG. 2(a) is a diagram in which the second particle 20 is directly attached to the (001) surface of the first particle 10, and the perimeter L is measured as shown by the dotted line. FIG. 2(b) is a diagram in which the second particle 20 is directly attached to the (100) surface of the first particle 10, and the perimeter L is measured as shown by the dotted line. FIG. 2(c) is a diagram in which the first second particle 20 is directly attached to the (001) surface of the first particle 10, and the second second particle 20 is attached so as to be in contact with the first particle 10 and the first second particle 20. In the example shown in (c) of FIG. 2, there is a space formed by the first particle 10 and two second particles 20, but the perimeter L is the perimeter of the composite particle and is measured as shown by the dotted line. (d) of FIG. 2 is a diagram in which the first second particle 20 is directly attached to the (001) face of the first particle 10 at its (001) face, and the second second particle 20 is directly attached to the (001) face of the first second particle 20 at its (001) face, and the perimeter L is measured as shown by the dotted line. Note that, according to the manufacturing method of boron nitride composite particles according to the present disclosure described later, composite particles in which the second particle 20 is attached to the first particle 10 mainly in the manner shown in (a) are obtained, rather than composite particles in which the second particle 20 is attached to the first particle 10 in the manner shown in (c) and (d) of FIG. 2. In addition, since the first particle 10 and the second particle 20 are close to each other and attached to each other by intermolecular interaction, the manner in which the second particle 20 is attached to the first particle 10 in the manner shown in (b) of FIG. 2 does not usually occur.
[0034] FIG. 3 is a schematic cross-sectional view for explaining the total value of the length of the (100) plane of the first particle 10 and the length of the (100) plane of the second particle 20 in a boron nitride composite particle. (a) of FIG. 3 is an example in which three second particles are directly attached to the (001) plane of one first particle 10 only through their (001) planes. In this case, the total value of the length 10a of the two (100) planes of the first particle 10 and the length 20a of the two (100) planes of each of the second particles 20 corresponds to the above total value. (b) of FIG. 3 is an example in which there is a space formed by the first particle 10 and two second particles 20, as in (c) of FIG. 2. In this case, the side surface 20b of the second particle 20 facing inward of the above space is also included in the above total value. Since the schematic diagram shown in Figure 3 is drawn in cross section of the composite particle, the above space appears to be closed to the outside, but it is a space that can be filled with resin, and the side surface 20b of the second particle 20 can also contribute to affinity with the resin.
[0035] The thickness of the boron nitride composite particle 100 is larger than that of the primary particle of hexagonal boron nitride because the second particle 20 is attached on the (001) face of the first particle 10. The average thickness of the boron nitride composite particle 100 is 0.5 μm or more. The lower limit of the average thickness of the boron nitride composite particle 100 may be, for example, 0.7 μm or more, 1.0 μm or more, or 1.5 μm or more. When the lower limit of the average thickness is within the above range, the number of functional groups per boron nitride composite particle 100 can be increased, the affinity with resins and the like can be further improved, and the heat dissipation property can be further improved when a resin composition is prepared. The upper limit of the average thickness of the boron nitride composite particle 100 may be, for example, 3.0 μm or less, 2.5 μm or less, or 2.0 μm or less. By setting the upper limit of the average thickness within the above range, when the boron nitride composite particles are dispersed in a resin and molded, the boron nitride composite particles are oriented, and the surface smoothness of the molded product can be improved. The average thickness of the boron nitride composite particles 100 can be adjusted within the above range, and may be, for example, 0.5 to 3.0 μm, 1.0 to 2.5 μm, or 1.5 to 2.0 μm.
[0036] The thickness of the boron nitride composite particle 100 means a value measured based on the following method. Specifically, first, 3 g of boron nitride composite particles are molded to 30 mmφ at a pressure of 5 MPa using a press molding machine, and then embedded in resin to form a molded body. The obtained molded body is subjected to cross-sectional milling in a direction parallel to the direction of pressure application to obtain a cross-section of the boron nitride composite particle. Since the boron nitride composite particles are oriented in one direction by press molding, measurement errors caused by the particles being tilted relative to the measurement surface can be suppressed. The cross-section obtained by cross-sectional milling is photographed using a scanning electron microscope, and the SEM image containing the obtained particle image is imported into image analysis software. Next, the thickness of the boron nitride composite particle is measured from the obtained SEM image. The same measurement is performed on 100 boron nitride composite particles, and the arithmetic average value is taken as the thickness of the boron nitride composite particle. As the press molding machine, for example, "BRE-32" (trade name) manufactured by Rigaku Corporation can be used. As the resin, for example, "G2 Epoxy" (product name) manufactured by GATAN Corporation can be used. As the scanning electron microscope, for example, "JSM-6010LA" (product name) manufactured by JEOL Ltd. can be used. As the image analysis software, for example, "Mac-View" (product name) manufactured by Mountech Co., Ltd. can be used.
[0037] From the viewpoint of improving the affinity with the resin, the first particle 10 and at least a part of the second particle 20 may be in a form in which the (001) planes contact each other. It is desirable that 50% or more of the second particle 20 are attached to the (001) plane of the first particle 10, and it is desirable that all of the second particles 20 are attached to the (001) plane of the first particle 10. By contacting the (001) planes of the first particle 10 and the second particle 20, the adhesion between the two particles becomes stronger, and the (100) plane of the second particle 20 attached to the first particle 10 can be directed to the outside of the boron nitride composite particle 100, and the affinity between the obtained boron nitride composite particle 100 and the resin can be further improved.
[0038] The average particle size of the first particle 10 may be, for example, 20.0 μm or less, 18.0 μm or less, 15.0 μm or less, or 10.0 μm or less. When the upper limit of the average particle size of the first particle 10 is within the above range, the ratio of the side surface present per boron nitride composite particle 100 can be further increased. The lower limit of the average particle size of the first particle 10 may be, for example, 2.0 μm or more, 3.0 μm or more, 4.0 μm or more, or 5.0 μm or more. When the lower limit of the average particle size of the first particle 10 is within the above range, the dispersibility of the obtained boron nitride composite particle 100 in the resin can be further improved. The average particle size of the first particle 10 may be adjusted within the above range, and may be, for example, 2.0 to 20.0 μm, 3.0 to 18.0 μm, or 3.0 to 15.0 μm.
[0039] The average particle size of the first particles 10 in this specification means a value measured using a particle size distribution measuring device in accordance with ISO 13320:2009. The average particle size obtained by the above measurement is an average particle size based on volume statistics, and the average particle size is a median value (d50). When measuring the particle size distribution, water is used as a solvent for dispersing the aggregates, and hexametaphosphoric acid is used as a dispersant. In this case, the refractive index of water is 1.33, and the refractive index of the hexagonal boron nitride powder is 1.80. As the particle size distribution measuring device, for example, "MT3300EX" (product name) manufactured by Nikkiso Co., Ltd. can be used.
[0040] The number of the second particles 20 attached to each of the first particles 10 can be adjusted according to the application of the boron nitride composite particle 100. The lower limit of the number of the second particles 20 attached to the first particle 10 may be, for example, 30 or more, or 40 or more per first particle, but from the viewpoint of further improving the effect of attaching the second particles, it may be 50 or more, 75 or more, or 100 or more. When the lower limit of the number of the second particles 20 attached to the first particle 10 is within the above range, the average thickness of the boron nitride composite particle 100 tends to increase, and the proportion of the (100) plane in the boron nitride composite particle 100 is improved, so that the affinity to resins and the like can be further improved. The upper limit of the number of the second particles 20 attached to the first particle 10 may be, for example, 200 or less, 150 or less, or 125 or less per first particle. When the upper limit of the number of the second particles 20 attached to the first particle 10 is within the above range, an increase in the specific surface area of the boron nitride composite particle 100 is suppressed, and a decrease in the dispersibility of the boron nitride composite particle 100 in the resin can be suppressed. The number of the second particles 20 attached to the first particle 10 may be adjusted within the above range, and may be, for example, 50 to 200, 75 to 150, or 100 to 125 per first particle. When the total value of the length of the (100) plane of the first particle 10 and the length of the (100) plane of the second particle 20 relative to the perimeter in a cross section perpendicular to the (001) plane of the first particle 10 is approximately the same, the boron nitride composite particle 10 can be expected to have a further affinity improvement effect by adjusting the number of the second particles 20 attached to each first particle 10.
[0041] The number of the second particles 20 attached to each of the first particles 10 means a value measured by the following method. Specifically, an SEM image of the boron nitride composite particle is obtained by a scanning electron microscope, and the number of the second particles attached to each of the boron nitride composite particles is measured. The same measurement is performed on 50 boron nitride composite particles, and the arithmetic average value is taken as the number of the second particles attached to each of the first particles. The measurement is performed on one of the main surfaces of the first particles observed in the SEM image obtained by the above method. As the scanning electron microscope, for example, "JSM-6010LA" (product name) manufactured by JEOL Ltd. can be used.
[0042] The above-mentioned boron nitride composite particles can be manufactured, for example, by the following method. One embodiment of the method for manufacturing boron nitride composite particles includes a step of dispersing a powder containing first particles of hexagonal boron nitride and second particles of hexagonal boron nitride having a particle size smaller than that of the first particles in a solvent containing an alcohol having 5 or less carbon atoms to obtain a dispersion (hereinafter also referred to as a dispersion step), and a step of reducing the content of the solvent from the dispersion and attaching one or more of the second particles onto the (001) plane of the first particles to obtain composite particles (hereinafter also referred to as a composite step).
[0043] The first and second particles of hexagonal boron nitride may be commercially available primary particles of hexagonal boron nitride, or may be separately prepared. The primary particles of hexagonal boron nitride may be prepared, for example, by the following method. The method for preparing the primary particles of hexagonal boron nitride includes a calcination step of obtaining a calcined product containing at least one selected from the group consisting of low-crystalline hexagonal boron nitride and amorphous hexagonal boron nitride by calcining a raw material powder containing a powder of a compound containing boron and a powder of a compound containing nitrogen in an inert gas atmosphere, an ammonia gas atmosphere, or a mixed gas atmosphere of these at a temperature of 600 to 1300 ° C., a calcination step of obtaining a calcined product by calcining a mixed powder containing the calcined product and an auxiliary in an atmosphere containing at least one of an inert gas and an ammonia gas at a temperature of 1600 ° C. or more and less than 2100 ° C., and a purification step of pulverizing, washing, and drying the calcined product to obtain a dry powder. In the pulverization step, the boron nitride baked in the firing step is disintegrated or pulverized. As the pulverization device, for example, a grinder mill, a roller mill, or the like can be used. In the pulverization step, the above-mentioned pulverization device is used to apply a shear force or a compression force, etc., so that each primary particle of boron nitride can be disintegrated or pulverized while maintaining its shape. According to the above-mentioned preparation method, the occurrence of cracks or chips in boron nitride can be suppressed, and a decrease in dispersibility in resin due to an increase in the specific surface area can also be suppressed.
[0044] The lower limit of the amount of the second particles may be, for example, 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more, relative to 100 parts by mass of the first particles. By setting the lower limit of the amount of the second particles within the above range, the ratio of the second particles adhering to the first particles can be improved, and the total value of the length of the (100) face of the first particles and the length of the (100) face of the second particles relative to the perimeter in a cross section perpendicular to the (001) face of the first particles can be improved. The upper limit of the amount of the second particles may be, for example, 50 parts by mass or less, 40 parts by mass or less, or 30 parts by mass or less, relative to 100 parts by mass of the first particles. By setting the upper limit of the amount of the second particles within the above range, adhesion between the second particles can be suppressed. The amount of the second particles can be adjusted within the above range, and may be, for example, 10 to 50 parts by mass, relative to 100 parts by mass of the first particles.
[0045] The content of the alcohol in the solvent may be, for example, 50% by volume or more, or 75% by volume or more, or may be 100% by volume (meaning that the solvent consists of the alcohol). When the content of the alcohol in the solvent is within the above range, the dispersion state of the secondary particles of hexagonal boron nitride can be made more uniform, making it easier to produce composite particles.
[0046] The carbon part constituting the alcohol having 5 or less carbon atoms may be linear, branched, or cyclic, but from the viewpoint of improving the dispersibility of the primary particles of hexagonal boron nitride, it is more preferable that it is linear. The number of carbon atoms constituting the alcohol may be, for example, 4 or less, 3 or less, or 2 or less, and may be 2. More specifically, the alcohol may include at least one selected from the group consisting of ethanol, 1-propanol, and 2-butanol, may include ethanol, or may be ethanol. By including the above-mentioned alcohol as the alcohol when preparing the dispersion, it is possible to suppress aggregation of the second particles having a small particle size in the dispersion, and to facilitate adhesion between the (001) planes of the first particles and the second particles.
[0047] The step of obtaining the dispersion may be a step of mixing the powder with the solvent and performing a dispersion treatment for 30 minutes or more. The dispersion treatment may be, for example, ultrasonic treatment, wet mixing, or the like.
[0048] In the composite step, the content of the solvent is reduced from the dispersion liquid, and one or more of the second particles are attached onto the (001) faces of the first particles. The means for removing the solvent may be, for example, heating, drying under reduced pressure, freeze-drying, or the like.
[0049] The above-mentioned boron nitride composite particles can improve the affinity with resin, and therefore can also be used as a filler for a resin composition. One embodiment of the resin composition contains a resin and the above-mentioned boron nitride composite particles.
[0050] Examples of resins include liquid crystal polymers, fluororesins, silicone resins, silicone rubber, acrylic resins, polyolefins (polyethylene, etc.), epoxy resins, phenolic resins, melamine resins, urea resins, unsaturated polyesters, polyimides, polyamideimides, polyetherimides, polybutylene terephthalate, polyethylene terephthalate, polyphenylene ether, polyphenylene sulfide, wholly aromatic polyesters, polysulfones, polyethersulfones, polycarbonates, maleimide-modified resins, ABS (acrylonitrile-butadiene-styrene) resins, AAS (acrylonitrile-acrylic rubber-styrene) resins, and AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resins.
[0051] The lower limit of the content of the boron nitride composite particles may be, for example, 30 volume % or more, 40 volume % or more, or 50 volume % or more based on the total volume of the resin composition. The upper limit of the content of the boron nitride composite particles may be, for example, 85 volume % or less, 80 volume % or less, 75 volume % or less, or 70 volume % or less based on the total volume of the resin composition.
[0052] The resin composition may contain other components in addition to the resin and the boron nitride composite particles. The other components may be, for example, a curing agent for curing the resin, a metal coupling agent, an inorganic filler, and the like.
[0053] The curing agent may be appropriately selected according to the type of resin. For example, when the resin is an epoxy resin, the curing agent may be, for example, a phenol novolac compound, an acid anhydride, an amino compound, and an imidazole compound. The content of the curing agent may be, for example, 0.5 parts by volume or more, or 1.0 parts by volume or more, and 15.0 parts by volume or less, or 10.0 parts by volume or less, relative to 100 parts by volume of the resin.
[0054] Since the resin composition contains the boron nitride composite particles according to the present disclosure, it is not necessary to contain a metal coupling agent. However, when the resin composition is used in a manner that allows the inclusion of other components, it is preferable to contain a metal coupling agent from the viewpoint of further improving the affinity between the resin and the boron nitride composite particles. Examples of the metal coupling agent include silane coupling agents, titanate coupling agents, and aluminate coupling agents. The content of the metal coupling agent may be 0.1 parts by mass or more, or 0.2 parts by mass or more, and 3.0 parts by mass or less, or 2.0 parts by mass or less, relative to 100 parts by mass of the boron nitride composite particles.
[0055] The above-mentioned resin composition can be used, for example, to form a sheet, and the obtained molded plate can be bonded to a different material such as a metal plate to form a laminate. The different material means a material different from the molded body molded by the resin composition. Examples of the different material include metal and ceramic sintered body. The shape of the different material is not particularly limited, but may be a plate shape or the like.
[0056] The laminate can be used, for example, in heat dissipation members. The laminate has a high affinity between the resin and the boron nitride composite particles in the molded product obtained by molding the resin composition, so that even if thermal stress or the like occurs, damage inside the molded product can be suppressed. In other words, by using the resin composition, a heat dissipation member having excellent durability can be molded.
[0057] Although several embodiments of the present disclosure have been described above, the present disclosure is not limited to the above-described embodiments. In addition, the contents of the descriptions of the above-described embodiments can be mutually applied. EXAMPLES
[0058] The present disclosure will be described in more detail below using examples and comparative examples. Note that the present disclosure is not limited to the following examples.
[0059] Example 1 [Preparation of primary particles of hexagonal boron nitride] 100.0 parts by mass of boric acid powder (purity: 99.8% by mass or more, manufactured by Kanto Chemical Co., Ltd.) and 90.0 parts by mass of melamine powder (purity: 99.0% by mass or more, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed for 10 minutes using an alumina mortar to obtain a mixed raw material. The dried mixed raw material was placed in a container made of hexagonal boron nitride and placed in an electric furnace. While circulating nitrogen gas in the electric furnace, the temperature was raised from room temperature to 1000°C at a rate of 10°C / min. After holding at 1000°C for 2 hours, heating was stopped and the material was allowed to cool naturally. When the temperature reached 100°C or less, the electric furnace was opened. In this way, a calcined product containing low-crystalline hexagonal boron nitride was obtained.
[0060] 3.0 parts by mass of sodium carbonate (purity: 99.5% by mass or more) was added as an auxiliary agent to 100.0 parts by mass of the above-mentioned calcined product, and the mixture was mixed for 10 minutes using an alumina mortar to obtain a mixture. The above-mentioned mixture was placed in a container made of hexagonal boron nitride and placed in the above-mentioned electric furnace. While circulating nitrogen gas in the electric furnace, the temperature was increased from room temperature to 1700°C at a rate of 10°C / min. After maintaining the firing temperature of 1700°C for 4 hours, heating was stopped and the mixture was allowed to cool naturally. When the temperature reached 100°C or less, the electric furnace was opened. The obtained fired product was collected and pulverized in an alumina mortar for 3 minutes to obtain coarse powder of hexagonal boron nitride.
[0061] Furthermore, in order to remove impurities contained in the hexagonal boron nitride, the coarse powder was added to dilute nitric acid so that 500 parts by mass of 5% dilute nitric acid was used per 30 parts by mass of the coarse powder, and stirred at room temperature for 60 minutes. Thereafter, solid-liquid separation was performed by suction filtration, and the filtrate was washed by replacing the water until it became neutral (until the electrical conductivity became 1ms / m or less). The washed powder was dried in a dryer at 170°C for 12 hours to prepare primary particles of hexagonal boron nitride. The obtained primary particles of hexagonal boron nitride had an average particle size of 6.0 μm.
[0062] [Preparation of secondary particles of hexagonal boron nitride] 100.0 parts by mass of boric acid powder (purity: 99.8% by mass or more, manufactured by Kanto Chemical Co., Ltd.) and 90.0 parts by mass of melamine powder (purity: 99.0% by mass or more, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed for 10 minutes using an alumina mortar to obtain a mixed raw material. The dried mixed raw material was placed in a container made of hexagonal boron nitride and placed in an electric furnace. While circulating nitrogen gas in the electric furnace, the temperature was raised from room temperature to 1000°C at a rate of 10°C / min. After holding at 1000°C for 2 hours, heating was stopped and the material was allowed to cool naturally. When the temperature reached 100°C or less, the electric furnace was opened. In this way, a calcined product containing low-crystalline hexagonal boron nitride was obtained.
[0063] 3.0 parts by mass of sodium carbonate (purity: 99.5% by mass or more) was added as an auxiliary agent to 100.0 parts by mass of the above calcined product, and mixed for 10 minutes using an alumina mortar to obtain a mixture. The above mixture was placed in a container made of hexagonal boron nitride and placed in the above electric furnace. While circulating nitrogen gas in the electric furnace, the temperature was increased from room temperature to 1600°C at a rate of 10°C / min. After maintaining the firing temperature of 1600°C for 4 hours, heating was stopped and the mixture was allowed to cool naturally. When the temperature reached 100°C or less, the electric furnace was opened. The obtained fired product was collected and pulverized with a jet mill to obtain coarse powder of hexagonal boron nitride.
[0064] Furthermore, in order to remove impurities contained in the hexagonal boron nitride, the coarse powder was added to dilute nitric acid so that 500 parts by mass of dilute nitric acid of 5% by mass was used for 30 parts by mass of the coarse powder, and stirred at room temperature for 60 minutes. Thereafter, solid-liquid separation was performed by suction filtration, and the filtrate was washed by replacing the water until it became neutral (until the electrical conductivity became 1ms / m or less). The washed powder was dried in a dryer at 170°C for 12 hours to prepare secondary particles of hexagonal boron nitride. The obtained secondary particles of hexagonal boron nitride had an average particle size of 1.0 μm.
[0065] [Preparation of dispersion] 100 parts by mass of the first particles of hexagonal boron nitride and 30 parts by mass of the second particles of hexagonal boron nitride were weighed out and placed in a container to prepare a mixed powder. 500 parts by mass of a dispersion medium (a mixture of ethanol and water at a volume ratio of 1:1) was added to 100 parts by mass of the mixed powder to prepare a mixed liquid. Next, 100 mL of the mixed liquid was weighed out and placed in a 300 mL beaker, and ultrasonically dispersed for 2 minutes using a homogenizer (manufactured by SONICS, product name: VC-505). After that, the mixture was stirred and dispersed for 30 minutes at 300 rpm using a three-one motor stirrer to prepare a dispersion.
[0066] [Preparation of boron nitride composite particles] The dispersion liquid prepared as described above was heated at 100° C. for 24 hours in an air atmosphere to remove the solvent, thereby obtaining powdered boron nitride composite particles.
[0067] <Evaluation of boron nitride composite particles> For the obtained boron nitride composite particles, the sum of the length of the (100) face of the first particle and the length of the (100) face of the second particle relative to the perimeter, the average thickness of the boron nitride composite particle, and the number of attached second particles were determined based on the method described below.
[0068] [Determination of the sum of the (100) plane lengths and the thickness of boron nitride composite particles] A scanning electron microscope was used to obtain an SEM image of the cross section of the boron nitride composite particle, and the total length of the (100) plane of the first particle and the (100) plane of the second particle relative to the perimeter and the average thickness of the boron nitride composite particle were determined by image analysis. Specifically, 3 g of boron nitride composite particles were molded to 30 mmφ at a pressure of 5 MPa using a press molding machine (manufactured by Rigaku Corporation, product name: BRE-32), and embedded in resin (manufactured by GATAN, product name: G2 epoxy) to obtain a molded body. The obtained molded body was subjected to cross-sectional milling in a direction parallel to the direction in which pressure was applied, to obtain a cross section of the boron nitride composite particle, which was used as the measurement subject. The cross section obtained by cross-sectional milling was photographed using a scanning electron microscope (manufactured by JEOL Ltd., product name: JSM-6010LA), and the obtained SEM image including the particle image was imported into image analysis software (manufactured by Mountec, product name: Mac-View). Next, the average thickness of the boron nitride composite particles, the perimeter of the boron nitride composite particles, the length of the (100) plane of the first particle, and the length of the (100) plane of the second particle were measured from the captured images. Based on the measurement results obtained, the total value of the length of the (100) plane of the first particle and the length of the (100) plane of the second particle relative to the perimeter was calculated. Similar measurements were performed on 100 boron nitride composite particles, and the arithmetic average values were determined as the total value of the lengths of the (100) planes, and the thickness of the boron nitride composite particles. The results are shown in Table 1.
[0069] [Determination of the number of secondary particles attached] A scanning electron microscope (JEOL Ltd., product name: JSM-6010LA) was used to obtain SEM images of the boron nitride composite particles, and the number of secondary particles attached to each boron nitride composite particle was measured. The same measurement was performed on 50 randomly selected boron nitride composite particles, and the arithmetic average value was taken as the number of secondary particles attached to each primary particle.
[0070] <Evaluation of resin composition containing boron nitride composite particles: Heat dissipation evaluation> The thermal conductivity was measured using the obtained boron nitride composite particles. Specifically, 60 volume % of the boron nitride composite particles, 36 volume % of an epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name: Epicoat 807), and 4.0 volume % of a curing agent (manufactured by Nippon Gosei Kako Co., Ltd., product name: Acmex H-84B) were mixed to prepare a resin composition. Next, the resin composition was applied to a PET sheet to a thickness of 1.0 mm to form a coating film, and degassing was performed under reduced pressure of 500 PaA for 10 minutes. After that, the temperature was 150°C and the pressure was 160 kg / cm. 2 The sheet having the defoamed resin composition film was heated and pressed for 60 minutes under the above conditions to prepare a sheet-like molded product (resin sheet) having a thickness of 0.5 mm, which was used as the measurement subject. A sample having a size of 10 mm width x 10 mm x 0.5 mm thickness was cut out from the resin sheet and used as the measurement specimen to measure the thermal conductivity H (unit: W / (m K)). The thermal conductivity H (unit: W / (m K)) was calculated by the thermal diffusivity A (unit: m K) measured by the laser flash method using a xenon flash analyzer (manufactured by NETZSCH, product name: LFA447NanoFlash). 2 / sec), and density B (unit: kg / m 3 ), and the specific heat capacity C (unit: J / (kg K)) measured using a DSC measuring device (manufactured by Rigaku Corporation, product name: ThermoPlusEvo DSC8230), and were calculated from the relational equation H=A×B×C. The results are shown in Table 1.
[0071] Example 2 Powdered boron nitride composite particles were obtained in the same manner as in Example 1, except that the auxiliary agent used in preparing the first particles was changed to calcium carbonate (purity: 99.5% by mass or more) and the firing temperature was changed to 1950°C. The average particle size of the first particles obtained by the above changes was 14.0 µm. For the obtained boron nitride composite particles, the total length of the (100) faces, the thickness of the boron nitride composite particles, and the number of attached second particles were measured in the same manner as in Example 1, and the thermal conductivity was measured. The results are shown in Table 1.
[0072] Example 3 Powdered boron nitride composite particles were obtained in the same manner as in Example 1, except that the amount of the second particles of hexagonal boron nitride was changed to 50 parts by mass per 100 parts by mass of the first particles of hexagonal boron nitride. The total length of the (100) faces, the thickness of the boron nitride composite particles, and the number of attached second particles were measured for the obtained boron nitride composite particles in the same manner as in Example 1, and the thermal conductivity was evaluated. The results are shown in Table 1.
[0073] Example 4 Powdered boron nitride composite particles were obtained in the same manner as in Example 1, except that the firing temperature in preparing the secondary particles was set to 1650°C. The average particle size of the secondary particles obtained by the above change was 2.0 µm. For the obtained boron nitride composite particles, the total length of the (100) faces, the thickness of the boron nitride composite particles, and the number of attached secondary particles were measured in the same manner as in Example 1, and the thermal conductivity was measured. The results are shown in Table 1.
[0074] Example 5 Powdered boron nitride composite particles were obtained in the same manner as in Example 1, except that the dispersion medium was changed to 500 parts by mass of a mixture of ethanol and water at a volume ratio of 1:9 per 100 parts by mass of the mixed powder. For the obtained boron nitride composite particles, the total length of the (100) faces, the thickness of the boron nitride composite particles, and the number of attached secondary particles were measured in the same manner as in Example 1, and the thermal conductivity was also measured. The results are shown in Table 1.
[0075] Comparative Example 1 The thermal conductivity was measured using the primary particles alone prepared in Example 1 without adding the secondary particles as Comparative Example 1. The results are shown in Table 1.
[0076] [Table 1] [Industrial Applicability]
[0077] According to the present disclosure, it is possible to provide novel composite particles of boron nitride that are composed of boron nitride, have improved affinity with resin, and exhibit excellent heat dissipation when a resin composition is prepared. According to the present disclosure, it is also possible to provide a method for producing the composite particles described above. According to the present disclosure, it is also possible to provide a resin composition containing the composite particles described above. [Explanation of symbols]
[0078] 10...first particle, 20...second particle, 100...boron nitride composite particle.
Claims
1. First particles of hexagonal boron nitride; a plurality of second particles of hexagonal boron nitride having a particle size smaller than that of the first particle and attached to (001) faces of the first particle, the sum of the length of the (100) plane of the first particle and the length of the (100) plane of the second particle relative to the perimeter in a cross section perpendicular to the (001) plane of the first particle is 5.0% or more; Boron nitride composite particles having an average thickness of 0.5 μm or more.
2. The boron nitride composite particle according to claim 1 , wherein the first particle and at least a portion of the second particle are in contact with each other via their (001) faces.
3. 3. The boron nitride composite particle according to claim 1, wherein the first particles have an average particle size of 20.0 μm or less.
4. 4. The boron nitride composite particle according to claim 1, wherein the number of said second particles attached to said first particle is 50 or more per one said first particle.
5. A resin composition comprising a resin and the boron nitride composite particles according to any one of claims 1 to 4.
6. a step of dispersing a powder consisting of first particles of hexagonal boron nitride and second particles of hexagonal boron nitride having a particle size smaller than that of the first particles in a solvent containing an alcohol having a carbon number of 5 or less to obtain a dispersion; reducing the content of the solvent from the dispersion and attaching one or more of the second particles onto the (001) faces of the first particles to obtain composite particles; A method for producing boron nitride composite particles, wherein the dispersing comprises ultrasonic treatment.
7. The method according to claim 6 , wherein the step of obtaining the composite particle is a step of attaching the (001) face of the second particle to the (001) face of the first particle.
8. The method according to claim 6 or 7, wherein the content of the alcohol in the solvent is 50% by volume or more.
9. The method according to any one of claims 6 to 8, wherein the alcohol comprises at least one selected from the group consisting of ethanol, 1-propanol, and 2-butanol.
10. The method according to any one of claims 6 to 9, wherein the amount of the second particles is 10 to 50 parts by mass with respect to 100 parts by mass of the first particles.
11. The method according to any one of claims 6 to 10, wherein the step of obtaining the dispersion comprises mixing the powder with the solvent and carrying out a dispersion treatment for 30 minutes or more.
Citation Information
Patent Citations
Aluminum nitride-boron nitride composite powder and method for producing the same
JP2008001536A
Modified boron nitride, method for producing the same and composition
JP2015036361A
Resin composition for dielectric and high-frequency dielectric device
JP2015040296A
Thermal conductive particle composition, method for producing thermal conductive particle composition, thermal conductive resin composition, and thermal conductive resin cured body
JP2016155937A
Hexagonal crystal boron nitride powder and method for producing the same, and composition and heat dissipation member using the same
JP2019116401A